Effect of Submergence on Boron Fractions in Soils of Konkan Region of Maharashtra - and V.G. Salvi, M.C. Kasture*, D.P. Kalokhe (Journal of the Indian Society of Soil Science, 2019)
The present study was conducted to examine the effect of submergence on different fractions of boron (B) in soils of Konkan region of Maharashtra. Surface soil samples representing eight soil series namely, lateritic, medium black, manat, coarse shallow, coastal alluvial, coastal saline, reddish brown and acid sulphate soil were collected from different places of Konkan region of Maharashtra. The soils were subjected under submergence in pots in laboratory condition for four months equivalent to the life cycle of rice crop. Soil sampling was done at a fixed interval of 30 days and analyzed for different fractions of B. Results showed that under submerged soil conditions, readily soluble, specifically adsorbed, oxide bound, organically bounded and residual B varied from 0.36-1.98, 0.46-2.04, 56.1-57.1, 4.67-4.47 and 188.8-250.5 mg kg-1 soil, respectively from 30 days after submergence to 120 days after submergence The observations showed that there were significant changes in all the fractions of B due to submergence thus increasing its availability for plant use.